Tunable swelling of polymer composite - Chong, Chun Wei (Nanyang Technological University, 2023)
Polymer blends, mixing functional materials with polymer matrices, have been considered an effective material design concept. It not only maintains the flexibility of polymer substrates but also endows novel functions to the sample. Water Swellable Rubber (WSR) is a typical polymer blend, which is formed by hybrid hydrophilic materials with polymer. The formed polymer composites have demonstrated many merits, such as high swelling capacity and rate, cost-effectiveness, so they have been utilized in multiple applications, including water-blocking cables and pipes to prevent water intrusion, sealing of concrete joints and cracks to prevent water penetration. However, there are still existing some limitations for conventional WSR, i.e., limited swelling capacity and slow swelling rate. In this study, we design a novel WSR with larger swelling ratio and high mechanical stiffness via introducing some soluble powders, e.g., sodium chloride (NaCl) and calcium chloride (CaCl2) into polymer matrix. Moreover, the effect of dimension and concentration of these soluble powders in the polymer composite were systematically investigated. We noticed that the sample exhibits different swelling ratio when the particle size, concentration and environment vary after soaking in deionized (DI) water. The rational explanation for above swelling is that the osmosis and capillary forces interactions with both filler and silicone substrate. Based on our results, we can obtain various swollen polymer samples by regulating the size, concentration, and environment of the soluble particles in the blend system. This study investigated the impact of particle size and concentration, which is a crucial processing factor, on polymer swelling, surface roughness, and mechanical properties.